2022
DOI: 10.5306/wjco.v13.i10.762
|View full text |Cite
|
Sign up to set email alerts
|

Systems biology and OMIC data integration to understand gastrointestinal cancers

Abstract: Gastrointestinal (GI) cancers are a set of diverse diseases affecting many parts/ organs. The five most frequent GI cancer types are esophageal, gastric cancer (GC), liver cancer, pancreatic cancer, and colorectal cancer (CRC); together, they give rise to 5 million new cases and cause the death of 3.5 million people annually. We provide information about molecular changes crucial to tumorigenesis and the behavior and prognosis. During the formation of cancer cells, the genomic changes are microsatellite instab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 145 publications
0
2
0
Order By: Relevance
“…However, it has been demonstrated in gastric cancer with bone metastases [12]. Activation of altered signaling cascades, particularly PIK3/AKT/mTOR, was combined with the identified changes, making them potential targets for antitumor therapy [13,14]. In this study, it was observed that there is an increase in PD-1 receptor expression when there is PIK3CA mutation present, which could be accompanied by changes in tumor immunogenic properties.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…However, it has been demonstrated in gastric cancer with bone metastases [12]. Activation of altered signaling cascades, particularly PIK3/AKT/mTOR, was combined with the identified changes, making them potential targets for antitumor therapy [13,14]. In this study, it was observed that there is an increase in PD-1 receptor expression when there is PIK3CA mutation present, which could be accompanied by changes in tumor immunogenic properties.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, the identified changes were combined with changes in signaling pathway activation. The PIK3/AKT/mTOR pathway might be considered as a potential target of antitumor therapy [13,14]. mTOR mediates PD-L1 expression in GCs [15,16], which was found to be associated with MUC16 mutation [17].…”
Section: Introductionmentioning
confidence: 99%